Proliferaciones algales de la diatomea toxigénica Pseudo-Nitzschia (Bacillariophyceae) en el Golfo de Nicoya, Costa Rica - Vargas-Montero, Maribelle (2004)
Water samples were collected during a red tide event in November 2001, near San Lucas Island (Gulf of Nicoya, Costa Rica). Superficial temperature was 27ºC and water was turbid, with no fetid smell. One sample was treated with negative staining and observed using a transmission electron microscope (TEM); another sample was observed using a scanning electron microscope (SEM). Samples had high concentrations of the diatom Pseudo-Nitzschia pungens f. pungens (characterized by two rows of poroids in the external channel), and lower concentrations of Skeletonema costatum (chains joined by external microtubules) and Chaetoceros lorenzianus (oval apertures and long chains, having setae with distinctive transverse rows and spines). This is the first time that the first species was described producing red tides in Costa Rica. However, reports about red tides with high concentration of species like P. pungens (variety multiseries) are increasing. These species have been related to the production of domoic acid, a low molecular weight amino acid which in humans can cause amnesic intoxications with seafood. Previously, Costa Rican reports of toxic accidents only referred to seafood contaminated with Pyrodinium bahamense var. compressum and Gymnodinium catenatum dinoflagellates. The increase in the number of Pseudo-Nitzschia causing harmful algae blooms is of interest for scientists around the world and must be documented. Similarly, some Chaetoceros species have been reported to be harmful to fish. We strongly recommend the establishment of a permanent surveillance program monitoring the presence of these species new at Costa Rican Pacific coast. Since the amnesic toxin is soluble in water and heat-resistant, we want to stress the possibility of having human cases of amnesic intoxication.